Immunological Efficiency of Human Plague Vaccination in the Gorno-Altai High-Mountain Natural Plague Focus - K. M. Korytov; V. V. Voitkova; V. I. Dubrovina; A. K. Noskov; A. I. Mishchenko; E. P. Mikhailov; S. V. Balakhonov; L. V. Schuchinov (Эпидемиология и вакцинопрофилактика, 2019)
Background. Plague is a dangerous natural-focal bacterial disease that can cause emergencies of interstate significance. In 2014–2016, three bubonic plague cases were registered among local residents in the Republic Altai. This circumstance was the reason for implementation of complex preventive measures. Comprehensive studies of the immune status of humans vaccinated (revaccinated) with live plague vaccine are presented in this paper. These people constantly reside and work at the territory of Gorno-Altai  high-mountain natural plague focus. Methodology. The study of the clinical material (blood) from 60 volunteers included the determination of the functional activity of phagocytic cells, the production of IFN-γ, IL-4 and TNF-α  cytokines, the titre of specific IgG anti-bodies to the capsular antigen of the plague microbe and the concentrations of the main classes of immunoglobulins in blood serum by enzyme immunoassay,  as well as immunophenotyping  of blood lymphocytes through flow cytometry and the de-termination  of the alleles of HLA class II genes by a polymerase chain reaction. Results. The materials of these studies made it possible to determine a number of important parameters indicative of the cellular and humoral immunity activation in humans immunized against plague. Frequently occurring alleles of the HLA-DRB1, HLA-DQB1 and HLA-DQA1 genes were defined. Possible associations of these alleles with the levels of TNF-α  and IL-4 production, as well as with the relative content of T-helpers  and CD3-CD16+ cells were revealed. Conclusions. The obtained results indicate the immune reconstruction of the humans immunized against the plague. The immunological efficiency and safety of live plague vaccine were confirmed during the exacerbation of the epidemiological situation in active natural plague focus. Nevertheless, further immunological monitoring is necessary to fully characterize the immunological reactivity of the humans vaccinated (revaccinated) with live plague vaccine, and to improve the strategy for specific plague prevention in natural foci.